Causes and consequences of imitation. - Heyes, C (2001)
Recent behavioural and neuroscientific research concerning imitation has revealed evidence of experience-dependent imitation in chimpanzees and birds, wide ranging imitation deficits in autism, and unintentional imitation in adult humans. This review examines these findings and also evaluates evidence of neonatal imitation and intentional imitation in infancy, and evidence suggesting that the left inferior frontal gyrus is specialized for imitation. At the theoretical level, the empirical findings support the view that the perceptual-motor translation that is a unique and defining property of imitation depends primarily on direct links between sensory and motor representations established through correlated experience of observing movements and carrying them out.